2001
DOI: 10.1063/1.1399009
|View full text |Cite
|
Sign up to set email alerts
|

Can we make the SiC–SiO2 interface as good as the Si–SiO2 interface?

Abstract: A high-resolution neutron powder diffraction study of ammonia dihydrate ( ND 3 2D 2 O ) phase I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In contrast to the D it in the lower half of the SiC band gap, these states are observed only in the wide-band-gap polytypes of SiC. Apparently then, they cannot be derived from SiC conduction band states as suggested by theory [8] but, rather, have an energy level not immediately related to the SiC electron states. These states exhibit an acceptor-type electrical behaviour and account for negative charges often observed in the n-type 4H-SiC MOS capacitors and transistors.…”
Section: Energy Distribution Of Sic/sio 2 Interface Statesmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to the D it in the lower half of the SiC band gap, these states are observed only in the wide-band-gap polytypes of SiC. Apparently then, they cannot be derived from SiC conduction band states as suggested by theory [8] but, rather, have an energy level not immediately related to the SiC electron states. These states exhibit an acceptor-type electrical behaviour and account for negative charges often observed in the n-type 4H-SiC MOS capacitors and transistors.…”
Section: Energy Distribution Of Sic/sio 2 Interface Statesmentioning
confidence: 81%
“…This would make suboxide bonds inevitable, leading to a graded SiC-oxide transition with poor insulating properties. Moreover, it has been suggested that even in the absence of extrinsic contributions to the SiC/SiO 2 interface trap density, there will arise intrinsic states due to the perturbation of the SiC valence band states at the interface [8]. On the other hand, the experimental results reveal a clear trend of gradual improvement of the SiC/SiO 2 interface electrical properties as better (alternative) procedures are employed for SiC epitaxial layer growth, pre-oxidation surface preparation, oxidation parameters, and the post-oxidation treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen atoms omitted for clarity. Selected bond distances (Å) and angles (deg): Si(19). (b) The (SiO 2 ) 2 CO 2 model (optimized in C 2v symmetry).…”
mentioning
confidence: 99%
“…Silicon carbide (SiC), possessing native silicon dioxide (SiO 2 ), is regarded as a wide-band gap (WBG) semiconductor . However, its utility in electronic devices has been impeded by the poor SiC–SiO 2 interface quality. Consequently, investigations of the structural properties of the SiC–SiO 2 interfaces have been increasing. The possibility of the formation of crystalline phases for silicon oxycarbide (i.e., Si 2 CO 6 ) near the SiC–SiO 2 interfaces has been theoretically studied .…”
mentioning
confidence: 99%
“…The off-diagonal term U AB thus has not enough strength to push a state in the gap; we note that the situation changes, instead, at the polar, negatively charged Ga-terminated Si/ GaAs ͑100͒ interface, where the repulsive potential induced by the negative charge pushes the P Si-Ga state within the GaAs band gap. Similar considerations apply to other abrupt interfaces studied in the literature, [11][12][13][14][15][16]37 giving us confidence in the soundness of the above model description. We also note that estimates for the interface-bonding parameters may be obtained from relatively simple models, such as the tightbinding approach of Ref.…”
Section: Koster-slater Model For the Interface-state Problemmentioning
confidence: 58%